China caught hacking into other states' computers. (Tibetan Review: The Monthly Magazine on all Aspects of Tibet, 2007)
The article reports on the hacking of China into the government computer systems of other country. The countries including the U.S, Germany, France, Great Britain and New Zealand declare that their system has been hacked by Chinese military hackers. The scheme has led to the cyber attacks of the U.S. battle carrier fleet and France public Internet, as well as the destruction of the British government networks.